(untitled) (Journal of The Colloquium for Information Systems Security Education, 2015)
The demand for cybersecurity professionals continues to significantly outpace the supply with a projected worldwide shortage of two million by 2017. At the same time, there are large numbers of transitioning military personnel that have important technical skills that could be coalesced into addressing this demand. This paper examines the development and proposed deployment of a project to do just this: Cybersecurity Rapid Education Apprenticeship Training to Employment System (CREATES). Challenges and benefits are discussed.